UPAYA PENGGUNAAN SEPEDA KONVENSIONAL SEBAGAI TRANSPORTSI RAMAH LINGKUNGAN UNTUK TUJUAN SEKOLAH DI KOTA PALANGKA RAYA - Evita Panjaitan (INFO-TEKNIK, 2025)
The selection of the right mode of transportation is very important for students to reach school safely and on time. This research aims to identify what efforts can be made to encourage students to choose conventional bicycles as their preferred mode of transportation for school purposes. This research uses a survey method by distributing questionnaires to students in several schools. The data collected includes information about the modes of transportation used, the distance between home and school, transportation costs, and other factors that influence the choice of transportation mode. Data collection was conducted using the online platform Google Forms. The data was analyzed with the help of SPSS software to determine which variables are most significant in increasing the ose of bicycles as an enviromentanlly friendly transportation option for educational travel in the city of Palangka Raya for junior high and high school students. The main model used is the binomial logit model to determine the efforts in using environmentally friendly transportation modes, in this case, conventional bicycles. Based on the study results with 281 respondents, the variables affecting the choice of transportation modes for junior high and senior high school students are Environmental Concern and Ownership of a Conventional Bicycle. Keywords: Transportation mode choice, environmentally friendly, conventional bicycle